(untitled) (Majalah Kedokteran Bandung, 2026)
Chronic suppurative otitis media (CSOM) is a multifactorial inflammatory disease of the middle ear that may be influenced by chronic upper airway pathology, including nasal septum deviation, which can contribute to impaired ventilation of the Eustachian tube and persistence of infection. Several previous studies have demonstrated an association between CSOM and septal deviation. However, the relationship between specific types and directions of septum deviation and the radiologic extent of CSOM infection has not been clearly elucidated. This descriptive-analytical study evaluated medical record data from patients diagnosed with CSOM and nasal septum deviation at Dr. Hasan Sadikin Hospital Bandung, Indonesia, from 2023 to 2024. The radiologic extent of infection was evaluated using temporal bone CT scans and categorized based on the degree of middle ear and mastoid involvement, while the septum deviation type was determined according to the Mladina classification and its direction was also recorded. A total of 35 patients met the inclusion criteria. Most patients (80%) demonstrated grade 3 radiologic involvement, and Mladina type 2 was identified as the most common septal deviation pattern. Despite the predominance of certain deviation types in patients with higher radiologic grades, statistical analysis revealed no significant relationship between septum deviation type or direction and the degree of radiologic CSOM involvement (p>0.05). These findings suggest that, although septum deviation is frequently observed in patients with CSOM, its specific type and direction are not significantly associated with the extent of radiologic infection involvement in this study population.